Physiological Role of Intestinotropic Glucagon Like Peptides in Health and Disease - Putta, Swathi; Vudara, Sri Rekha; Kilari, Eswar Kumar (Asian Journal of Biological and Life Sciences, 2020)
Gastrointestinal hormones are the set of hormones which are secreted from the enteroendocrine cells of gastrointestinal tract. They coordinate functions like nutrient assimilation, food intake and signal transduction of various physiological processes. The remarkable enteroendocrine cells include enterochromaffin (EC) cells, enterochromaffin like (ECL) cells, G cells, D cells, M/Mo cells, S cells, K cells, I cells, N cells and L cells. Out of them, L cells in the ileum and colon secrete GLP-1, GLP-2, oxyntomodulin, peptide YY from glucagon coding gene (GCG) or proglucagon gene. GLP-1 is reported to perform functions like glycemia, glucose dependent insulin secretion, gastric emptying, regulation of food intake, β cell proliferation whereas GLP-2 is reported for variety of functions like regulation of mucosal growth in small and large intestine, enterocyte glucose transport nutrient absorption, inhibition of gastric emptying as well as gastric acid secretion, stimulation of intestinal blood flow, relaxation of intestinal smooth muscle. These intestinotropic glucagon like peptides channelize several homeostatic mechanisms and involve in the target specific actions all the way. The above mentioned functions of intestinotropic glucagon like peptides might be due torapid release by means of neural reflex and delayed release driven by the presence of food in the gut.
Keywords: Gastrointestinal hormones; GLP-1; GLP-2; Intestinotropic glucagon like peptides; L cells